THE EUROPEAN EXPLORATION TO THE NEW WOLRD (The First Permanent English Settlement as an American Milestone) - Yusuf, Muhammad (English Department of Faculty of Tarbiyah and Teachers Training, 2012)
ABSTRACTâThe pursuit of happinessâ was one of the spirit belonged to the European people in the Age of Exploration. This jargon was realized when the European lost their freedom to act, especially freedom to get better life and to embrace religious belief, hence, to have the freedom, they explored other hemisphere to reach their goal. The discussion is started by the description of England condition especially in the early of 17th century which pushed the English went out from their mother land. Jamestown conditions became pull factors, so they explored and tried to settle in it. This article will focus on push factors for the European exploring the New World. Push factors relate to the unstable condition of Europe especially in England such as religion, politics, and economy.